Dramatic secular changes in prognosis for kidney transplant candidates in the United States. Issue 2 (14th August 2018) - Schold, Jesse D.; Arrigain, Susana; Flechner, Stuart M.; Augustine, Joshua J.; Sedor, John R.; Wee, Alvin; Goldfarb, David A.; Poggio, Emilio D.
Abstract : Over recent decades, numerous clinical advances and policy changes have affected outcomes for candidates of kidney transplantation in the United States. We examined the national Scientific Registry for Transplant Recipients for adult (18+) solitary kidney transplant candidates placed on the waiting list for primary listing from 2001 to 2015. We evaluated rates of mortality, transplantation, and waitlist removal. Among 340 115 candidates there were significant declines in mortality (52 deaths/1000 patient years in 2001‐04 vs 38 deaths/1000 patient years in 2012‐15) and transplant rates (304 transplants/1000 patient years in 2001‐04 vs 212 transplants/1000 patient years in 2012‐15) and increases in waitlist removals (15 removals/1000 patient years in 2001‐04 vs 25/1000 patient years in 2012‐15) within the first year after listing. At 5 years an estimated 37% of candidates listed in 2012‐15 were alive without transplant as compared to 22% in 2001‐04. Declines in mortality over time were significantly more pronounced among African Americans, candidates with longer dialysis duration, and those with diabetes ( P  < .001). Cumulatively, results indicate dramatic changes in prognoses for adult kidney transplant candidates, likely impacted by selection criteria, donor availability, regulatory oversight, and clinical care. These trends are important considerations for prospective policy development and research, clinical and patient decision‐making, and evaluating the impact on access to care. Abstract : Dramatic secular changes in the last 15 years in mortality, transplant, and waitlist removal rates for kidney transplant candidates affect patients' prognosis and should be considered for decision‐making, research, and policy development. See Gupta and Abt's comments onpage 313 .